Analysis of the levitation force of pure and starch/polystyrene/MWCNT added bulk MgB2 superconductors using frozen image model under zero field cooling condition. (April 2016) - Tripathi, D.; Dey, T.K.
Highlights: First report on levitation force of starch/polystyrene/MWCNT added MgB2 under ZFC. Levitation force does not show any hysteretic behavior. Levitation force of MgB2  + 1 wt.% of polystyrene displays 20% enhancement. 'Modified frozen image model' explains well the experimental data. Vertical stiffness enhances sharply below 1.5 cm. Abstract: The measurement of superconducting levitation force between permanent magnet and polycrystalline samples of pure and MgB2 added with starch, polystyrene (PS) and multiwall carbon nanotube (MWCNT) have been performed under zero field cooling (ZFC) condition at 20 K in both descending and ascending modes. For this, the bulk pellets were synthesized by conventional solid state sintering technique. The XRD data indicate well developed MgB2 phase. However, a decrease in lattice parameter ' a  =  b ' have been observed for doped MgB2 samples. Superconducting transition temperature of MgB2 also decreases with starch/PS/MWCNT addition. Unlike MWCNT, the addition of starch/polystyrene is found to enhance the levitation force of MgB2 superconductor. The levitation force between PM and investigated pellets in ZFC condition is explained well in terms of the updated version of modified frozen image model and the magnetic moment originated due to vertical motion of the superconductors have been estimated. It may be noted that except for MWCNT, addition of starch/PS in MgB2 improves the magnetic moment generated by vertical movement of pure MgB2 . However, this improvement is more pronounced for 1 wt.% of PS added MgB2, which indicates more flux trapping and hence better levitation properties in 1 wt.% of PS added MgB2 . The vertical stiffness estimated for pure and starch/PS/MWCNT doped MgB2 samples indicate that the levitation force are more sensitive in the region close to the PM.